Improving Overhead Passing Skills In Volleyball Through The Cooperative Learning Model Type TPS (Think-Pair-Share) For 5th Grade Students At SDN Datengan 2 - Brilian Ahmad Firidaus; Anis Zawawi; Agus Cahyo Utomo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to improve overhead passing skills in volleyball through the Think-Pair-Share (TPS) cooperative learning model for 5th-grade students at SDN Datengan 2. This model was chosen because it allows students to think independently, discuss in pairs, and share their understanding in groups, which is expected to effectively enhance their passing skills. This research used the classroom action research (CAR) method, consisting of several cycles with planning, implementation, observation, and reflection stages. Data were collected through observations, passing skill tests, and student motivation questionnaires. The results showed that the TPS model improved students' overhead passing skills, active participation, and teamwork during learning activities. The conclusion of this study indicates that the TPS model is effective in enhancing students’ overhead passing techniques while also fostering social interaction and motivation. This method can be an alternative for teaching Physical Education, especially volleyball.